Microsoft Dynamics NAV - Diffenderfer, Paul M. (Springer, 2017)
Mastering Microsoft Dynamics NAV for beginners and IT professionals: from jump start to optimization. This book covers general use and shows you how to tailor Microsoft Dynamics NAV to mirror your firm's unique needs. Learn skills that enable you to navigate and interpret the world of possibilities locked within the ERP system. Through easy, concrete examples, you will master the layered environment and be able to use and create reports, forms, import/export functions and more. This book gives you the basis you need to demand the best information infrastructure for your enterprise. The 2nd edition is newly edited with an additional chapter on Dataports - the tool to use for the simple import/export of data or for the complex integration of Microsoft Dynamics NAV with other software and databases.